2014
DOI: 10.1021/ja504097v
|View full text |Cite
|
Sign up to set email alerts
|

Surface Plasmon-Driven Water Reduction: Gold Nanoparticle Size Matters

Abstract: Water reduction under two different visible-light ranges (λ > 400 nm and λ > 435 nm) was investigated in gold-loaded titanium dioxide (Au-TiO2) heterostructures with different sizes of Au nanoparticles (NPs). Our study clearly demonstrates the essential role played by Au NP size in plasmon-driven H2O reduction and reveals two distinct mechanisms to clarify visible-light photocatalytic activity under different excitation conditions. The size of the Au NP governs the efficiency of plasmon-mediated electron trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
273
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(302 citation statements)
references
References 46 publications
12
273
0
Order By: Relevance
“…Qian et al fabricated Au-TiO 2 heterostructures with AuNPs of different sizes, applying deposition-precipitation and photodeposition methods to commercial P25 TiO 2 . [45] The authors compared the hot electron conversion efficiency of 4.4 nm AuNPs with that of 67 nm AuNPs under λ > 435 nm illumination. Both 4.4 nm and 67 nm AuNPs could induce photodeposition of Pt nanoparticles on TiO 2 under illumination.…”
Section: Wwwadvopticalmatdementioning
confidence: 99%
See 1 more Smart Citation
“…Qian et al fabricated Au-TiO 2 heterostructures with AuNPs of different sizes, applying deposition-precipitation and photodeposition methods to commercial P25 TiO 2 . [45] The authors compared the hot electron conversion efficiency of 4.4 nm AuNPs with that of 67 nm AuNPs under λ > 435 nm illumination. Both 4.4 nm and 67 nm AuNPs could induce photodeposition of Pt nanoparticles on TiO 2 under illumination.…”
Section: Wwwadvopticalmatdementioning
confidence: 99%
“…Recently, TiO 2 -decorated plasmonic metal nanoparticles, such as AuNPs/TiO 2 , AuNRs/TiO 2 , and Au/TiO 2 Janus nanohybrids have been synthesized for photocatalytic water splitting. [45,48,56] In addition to TiO 2 , various semiconductors have also been used to prepare efficient photocatalytic systems. Primo et al synthesized a heterogeneous photocatalyst based on gold www.advopticalmat.de supported on nanoparticulate ceria (Au/CeO 2 ) for the generation of oxygen from water, [124] which exhibited a high photocatalytic activity for the solar water-splitting under visible light.…”
Section: Water Splittingmentioning
confidence: 99%
“…al. 36 found that small plasmonic Au particles cannot inject a sufficient number of hot electrons into the conduction band of TiO2 to raise the energy level sufficiently to drive the hydrogen evolution reaction (HER). DuChene et.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of the surface plasmon absorption is highly dependent on the type of metal, size, shape, surrounding dielectric medium, distance between neighboring objects, and configuration their ensemble [101]. A wide range of metal/semiconductor heterostructures, including Au/TiO 2 , Ag/TiO 2 , Au/CdS, and Au/Fe 2 O 3 , have been explored to achieve enhanced photocatalytic activity [102][103][104][105][106][107][108][109][110].…”
Section: The Plasmonic Metal Case: Plasmonic-metal/semiconductor Hetementioning
confidence: 99%